Rituximab‐combination chemotherapy achieves a 10th cycle of remission for Burkitt's lymphoma. Issue 2 (April 2015) - Umeda, Katsutsugu; Fujino, Hisanori; Saida, Satoshi; Kato, Itaru; Hiramatsu, Hidefumi; Yamada, Tomomi; Hori, Toshinori; Adachi, Souichi; Heike, Toshio; Watanabe, Ken‐Ichiro
Abstract A 14‐year‐old girl with multiple intra‐abdominal tumors was diagnosed with stage III Burkitt's lymphoma. She achieved complete remission after multi‐drug chemotherapy, but she relapsed after six courses. Autologous peripheral blood stem cells (PBSC) or allogeneic PBSC harvested from an HLA‐identical sibling were insufficient, and her family did not agree to bone marrow collection from the sibling. Although the patient relapsed nine times (the relapses involved intra‐abdominal organs or bone) during the following 4 years 7 months, treatment with rituximab monotherapy or in combination with ifosphamide, carboplastin, and etoposide, or local irradiation (33.8–40.0 Gy) to treat the bone metastases, proved effective, resulting in complete or partial remission. At the time of writing, the patient was in a 10th cycle of remission lasting 1 year 6 months and had not required transplantation. Thus, a chemotherapy regimen including rituximab might be effective for Burkitt's lymphoma in patients experiencing multiple relapse.